Triumph and torment ebook - Conway, Gerry (Marvel Worldwide, Inc., 2016)
Collects Doctor Strange and Doctor Doom: Triumph and Torment, Doctor Strange (1974) #57 and material from Astonishing Tales (1970) #8, Marvel Fanfare (1982) #16 and #43. Every year on Midsummer's Eve, Victor von Doom clashes with the forces of evil in a vain attempt to free his mother's soul from Hell. Only when Doctor Stephen Strange -- Master of the Mystic Arts and Earth's Sorcerer Supreme -- is convinced to join the fight, does the outcome have any hope of changing. But first these unlikely allies must journey to Mephisto's infernal realm ... where they find that the cost of one soul may be more than they are willing to pay!